The Impact of Quran Memorization on the Quality of Students’ Memorization - Athari, Zaifullah; Rahmi, Elvi; Alatise, Toyosi (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2023)
Quran memorization learning plays an important role in maintaining the purity and understanding of the Quran among students. However, the effectiveness of memorization activities in improving the quality of memorization has not been widely examined empirically, especially at the elementary school level. This study aims to examine the effect of Quran memorization activities on improving students’ memorization quality. A quantitative method with a descriptive approach was employed. Data were collected from 60 students in grades IV, V, and VI at an elementary school in during the 2023/2024 academic year using a total sampling technique. The results show that: i) the average Quran memorization score (variable X) was categorized as good, with a mean value of 70.55; ii) the average memorization quality (variable Y) was also in the good category, with a mean value of 48.2; and iii) Quran memorization had an effect on improving students’ memorization quality, with a coefficient of determination (R²) of 0.029 or a contribution of 2.9%, while the remaining 97.1% was influenced by other factors. These findings indicate that the effect of memorization activities on students’ memorization quality is relatively small but still provides a positive contribution. The results of this study may serve as a basis for future research to explore other factors that influence the quality of students’ Quran memorization.